Impact of the operating conditions on the derived products and the reaction mechanism in vacuum pyrolysis treatment of the organic material in waste integrated circuits. (1st October 2018) - Liu, Ya; Li, Kuo; Guo, Jie; Xu, Zhenming
Abstract: Recycling waste integrated circuits is significant for resource recovery and environmental protection. Integrated circuits are rich in metals including silver, copper and so on. However, it is difficult to recover metals from integrated circuits because they are tightly covered with packaging materials, which are mainly composed of organic material. The content of organic material in integrated circuits reaches up to 14.08 wt%, which should be removed beforehand for more effective recovery of metals and avoiding environmental pollution. But scant research has been done to study the reasonable treatment. In this study, vacuum pyrolysis was applied to degrade the organic material of waste integrated circuits. The organic conversion rate could reach 80.05% with the temperature of 615 °C, the pressure of 20 Pa and the holding time of 24 min. The effects of temperature and pressure on pyrolysis products were analyzed. Besides, the reaction mechanism in the process of vacuum pyrolysis was studied. The pyrolysis residue was crushed and screened after pyrolysis and it was concluded that metal concentrate and nonmetals accounted for 43.17% and 56.83%, respectively. And the rate of copper recovery reached 98.21%. This study provides an efficient process for the treatment of organic material in waste integrated circuits. Graphical abstract: Highlights: Organic packaging materials of waste integrated circuits was degraded efficiently by vacuum pyrolysis treatment. The mechanism of organic material degradation by vacuum pyrolysis was investigated. The effects of temperature and pressure on pyrolysis products were analyzed. The organic material was converted to char and oil. The pyrolysis residue was crushed and screened to recover metals.